Corrigendum to: “Multiple connections between Amazonia and Atlantic Forest shaped the phylogenetic and morphological diversity of Chiasmocleis Mehely, 1904 (Anura: Microhylidae: Gastrophryninae)” [Molecular Phylogenetics and Evolution, Volume 130, January 2019, Pages 198-210] - de Sá, Rafael O.; Tonini, João Filipe Riva; Huss, Hannahvan; Long, Alex; Cuddy, Travis; Forlani, Mauricio C.; Peloso, Pedro L.V.; Zaher, Hussam; Haddad, Célio F.B. [UNESP] (Elsevier, 2019)
Addendum to Multiple connections between Amazonia and Atlantic Forest shaped phylogenetic and morphological diversity in the genus Chiasmocleis Mehely, 1904 (Anura: Microhylidae: Gastrophryninae). Authors regret that once our recent work appeared as a prepublication on line (October, 2018; de Sá et al., 2019 “2018”), colleagues informed us that the name Relictus, which we applied to a basal lineage of Chiasmocleis, was preoccupied by a genus of North America fishes, Relictus Hubbs and Miller, 1972. Following Art. 67.8 of the ICIN, we replace the subgenus Relictus with the name Unicus, (latin meaning one of a kind, single, only, unique) and applied it to the lineage currently represented by Chiasmocleis gnoma Canedo et al., 2004. The authors would like to apologise for any inconvenience caused.